View with a grain of sand selected poems - Szymborska, Wislawa (Harcourt, 1995)
An anthology by a Polish writer. In Bodybuilders' Contest, she writes: "He grunts while showing his poses and paces. / His back alone has twenty different faces. / The mammoth fist he raises as he wins / is tribute to the force of vitamins." By the author of Sounds, Feelings, Thoughts.